Implementasi Software Accurate Online Pada Perusahaan - Maulana, Fajar; Arisman, Anton (Universitas Multi Data Palembang, 2024)
This research was produced using studies carried out at the Gudang Hikmat Foundation. Implementing and streamlining the accounting information system for the Gudang Hikmat Foundation's financial statement preparation is the aim of this study. Utilizing both primary and secondary data, this study employs qualitative research methodologies. The history of the Gudang Hikmat Foundation, its vision and mission, the financial statement preparation process, and the financial statement outcomes are the primary data in question; supplementary material comes from company documentation and interviews. The Gudang Hikmat Foundation's financial statement issues are described using a qualitative descriptive analysis approach as the data analysis method. According to the study's findings, Gudang Hikmat Foundation frequently encounters issues in creating financial reports needs an ineffective data input procedure that slows reporting and frequently results in human mistake when entering financial report data since financial reports are still created manually using Microsoft Excel. It is envisaged that by putting in place a system specifically designed to meet the objectives of the foundation, the process of creating accurate and comprehensive financial reports will become easier.